Depression, Aggression And Spiritual Well-Being Among The University Students In Jordan - Alorani, Omar Ismail; Alradaydeh, Muâ€™taz Fuad (European Scientific Journal, ESJ, 2017)
Background: University students have increased levels of depression and its complications. Aggression is a serious problem among the university students in Jordan, while spiritual well-being is associated with many psychosocial issues. The purpose of this study was to identify the relationship between depression, aggression, and spiritual well-being among the university students. Methods: A quantitative approach using cross-sectional descriptive-correlation design was used to carry out on convenience sample of 919 students at the University of Jordan. Results:Â  Almost 55.7% of the university students exhibited some degrees of depression. 51.3% of the students reported high aggression, while 48.7% of the students reported low aggression. The Pearson correlation coefficient test showed positive correlation between depression and aggression (r= .364, p< 0.001), and negative correlation between spiritual well-being and both of depression and aggression (r=-.533, r=-.288, p<0.001) respectively. Conclusions: Depression, aggression, and spiritual well-being were significantly correlated. Psychological counselors, social workers, and teachers at the universities should provide continuous psychological assessment and interventions for the students who reported high levels of aggression and depression. Spiritual well-being should be included in their interventions through various form of community services to enhance the sense of meaning of life, peace, and faith among university students.